THE INFLUENCE OF PARENTAL SUPPORT ON STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Fitri, Mainar; Susanti, Mirda Afrilia; Nurzena, Nurzena; Mirawati, Mirawati (Journal of English and Arabic Language Teaching, 2025)
Parental support is one of external factors that can influence students’ ’learning achievement.  Several studies have examined the influence of parental support on students’ achievement in learning Mathematics and Science subjects. A little attention has been given to English learning. To fill the gap, this study aimed to determine whether there is a significant influence of parental support on students' English learning achievement. The research method used was quantitative with an ex post facto design. The researchers selected 36 eighth-grade students at one of state junior high school in Riau Province, Indonesia as the sample by using a total sampling technique. Data were collected through a questionnaire to measure the level of parental support, while students' English learning achievement data were obtained from scores taken from documentation provided by the English teacher. The data were analyzed by using simple linear regression with the assistance of SPSS version 20.0. The results showed that the calculated t-value was greater than the t-table value, (3.103 > 2.032),   indicating that the alternative hypothesis was accepted. Therefore, it can be concluded that there is a significant influence of parental support on students’ English learning achievement. The influence of parental support on students’ English achievement was 22.1%. So, it is suggested that parents should give their support to their children in learning English to make their children get good achievement in learning English.